INTERNATIONAL AND NATIONAL FEATURES OF THE PRINCIPLES CORPORATE MANAGEMENT - DYKHNICH, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article reveals the essence of international principles of corporate governance in terms of forming effective relationships with clients, shareholders, suppliers, the public, state and local authorities. It was determined that the international principles of corporate governance are: protection of shareholders' rights; ensuring the equal treatment of shareholders, recognizing the rights of interested parties provided by law and encouraging active cooperation between the company and interested parties in creating welfare, jobs and ensuring the financial stability of the enterprise; ensuring timely and accurate coverage of information on all the most important issues related to the joint-stock company; ensuring strategic management of the company, effective supervision of the activities of executive directors, as well as reporting to the company and shareholders.A detailed analysis of the characteristics of the principles of corporate governance according to various systems was carried out, which proved that the principles of corporate governance of the Organization for Economic Cooperation and Development were adapted for countries in which there is a movement towards a market economy in order to cover various existing governance models.A comparison of international and national principles of corporate governance was made. The analysis of the application of the principles of corporate governance in the practice of management of Ukrainian corporations was carried out. It was determined that the principles of corporate governance that do not apply to modern enterprises include the following: participation of shareholders in decision-making, transparent capital structure, effective functioning of corporate control markets, equal treatment of owners of shares of the same type, participation of interested persons in the management of the corporation, access of interested parties persons to internal corporate information, high quality and reasonableness of information, annual audit by the auditor, the same attitude of the board to all shareholders.
Keywords: corporate governance; corporation; shareholders; investors; principles; efficiency; development